Combined Use of CytoSorb and ECMO in Patients with Severe Pneumogenic Sepsis - Akil, Ali; Ziegeler, Stephan; Reichelt, Jan; Rehers, Stephanie; Abdalla, Omer; Semik, Michael; Fischer, Stefan (The Thoracic and Cardiovascular Surgeon, 2020)
Background High morbidity and mortality are frequently reported in intensive care patients suffering from severe sepsis with systemic inflammation. With the development of severe respiratory failure, extracorporeal membrane oxygenation (ECMO) is often required. In this study, cytokine adsorption therapy in combination with ECMO is applied in patients with acute respiratory distress syndrome (ARDS) due to severe pneumogenic sepsis. The efficacy of this therapy is evaluated compared with a historical cohort without hemoadsorption therapy.Methods Between January and May 2018, combined high-flow venovenous ECMO and CytoSorb therapy (CytoSorb filter connected to ECMO circuit) was applied in patients (n = 13) with pneumogenic sepsis and ARDS. These patients were prospectively included (CytoSorb group). Data from patients (n = 7) with pneumogenic sepsis and ECMO therapy were retrospectively analyzed (control group).Results All patients survived in the CytoSorb group, where the 30-day mortality rate reached 57% in the control group. After CytoSorb therapy, we instantly observed a significant reduction in procalcitonin (PCT) and C-reactive protein (CRP) levels compared with the control group. Within 48 hours, the initial high doses of catecholamine could be weaned off only in the CytoSorb group.Conclusions Our results indicate that CytoSorb in combination with ECMO is an effective therapy to prevent escalation of sepsis with rapid weaning off high-dose catecholamine infusions and quick reduction in PCT and CRP levels. Optimal timing of immunomodulatory therapy and impact on ECMO-related inflammation still need to be furtherly investigated.
Keywords: extracorporeal membrane oxygenation; ECMO; inflammation; systemic; including cells; mediators; shock; systemic; cardiac; or circulatory